Simplified, High Drug‐Loaded Formulations Containing Hydrochlorothiazide for Twin‐Screw Granulation. Issue 8 (7th June 2017) - Meier, Robin; Moll, Klaus‐Peter; Krumme, Markus; Kleinebudde, Peter
Abstract: Simplified, high drug loaded formulations for use in twin‐screw granulation and tableting were introduced, using the plastically deforming drug ibuprofen. This concept was enlarged by application of hydrochlorothiazide, because opposed deformation behavior was expected to result in different product performances. In most instances the results differed. Critical quality attributes like granule size distribution, disintegration time, and tensile strength of tablets could be met. The study confirms the suitability of simplified formulation with differently behaving drugs for pharmaceutical product design in continuous manufacturing. Abstract : The study deals with extremely simplified and slimmed pharmaceutical formulations containing high loads of a brittle drug for continuous twin‐screw granulation. Resulting granules and tablets consistently corresponded to critical quality attributes, given by the authorities. Various disintegration and tensile strength profiles could be tailored.